Predicting Skin Flap Viability Using a New Intraoperative Tissue Oximetry Sensor: A Feasibility Study in Pigs - Lohman, Robert F.; Ozturk, Cemile Nurdan; Djohan, Risal; Tang, Hamilton Roger; Chen, Hui; Bechtel, Kate L. (Journal of Reconstructive Microsurgery, 2014)
Background Operations for soft-tissue reconstruction, orthopedic, vascular, and other types of surgery can be complicated by unexpected skin flap necrosis. At present, surgeons utilize subjective clinical judgment and physical findings to estimate the potential for tissue compromise. As the validity of these subjective methods is questionable, there is a need for objective, quantitative tools to determine the risk of flap necrosis during surgery.Methods Three 9-month-old Yorkshire pigs were used for the study. Four laterally based random pattern fasciocutaneous flaps were dissected on each animal. After the flaps were elevated, a prototype oximeter (ViOptix Inc., Fremont, CA), was used to measure tissue oxygenation (StO2) at 2 cm intervals along the flaps. Measurements were performed immediately after the flaps were dissected, and again at the same points after they were sutured. The animals were reevaluated 4 days later, and assessed for areas of tissue necrosis.Results For each flap, StO2 at the base was compared with StO2 at the more distal points. The median delta StO2, as measured immediately after dissection, was −3.9% points for tissue that remained viable and −34.0% points for tissue that became necrotic (p = 0.039). After the flaps were sutured back to the chest wall, the median delta StO2 for tissue that remained viable was −1.7% points versus −24.7% points for tissue that became necrotic (p = 0.006).Conclusions This new handheld surface sensor can be used to measure StO2 of skin flaps and may potentially reduce complications associated with unexpected tissue necrosis.
Keywords: tissue oximetry; flap perfusion; spectrophotometry